PERAN CORPORATE GOVERNANCE DALAM PRAKTIK RISK DISCLOSURE PADA PERBANKAN INDONESIA - Suhardjanto, Djoko; Dewi, Aryane; Rahmawati, Erna; M, Firazonia (JURNAL AKUNTANSI DAN AUDITING, 2012)
The purpose of this study is to examine the effect of corporate governance to risk disclosure ofIndonesian banks. Corporate governance are identified as the board size, the proportion ofindependent director, the proportion of woman director, the educational background of presidentdirector, the culture background of president director, the number of board meetings, the number ofaudit committee meetings and the proportion of independen audit committee members. This studyalso uses leverage and profitability as control variable. The level of risk disclosure is measuredbased on identified items of Lampiran Surat Edaran Bank Indonesia No.5/21/DPNP/2003. Underpurposive sampling, secondary data of 60 annual reports year 2007-2009 of banks in IndonesianStock Exchange are selected.The average level of risk disclosure is 51.42%. The result indicatesthat the level of risk disclosure of banking is at low since risk disclosure is mandatory disclosureaccording PSAK No. 31 (revised 2000), PBI Nomor: 5/8/PBI/2003, PSAK 50 (2006) andP3LKEPPBANK (2008). The result of multiple regression shows that corporate governance affectsthe level of risk disclosure through the variable board size and the number of board meetings. Othervariable, the proportion of independent director, proportion of woman director, educationalbackground of president director, culture background of president director, the number of auditcommittee meeting, and proportion of independen audit committee members are not goodpredictors for level of risk disclosure.Keywords:risk disclosure, corporate governance, Indonesian banks